2017
DOI: 10.13075/ijomeh.1896.01052
|View full text |Cite
|
Sign up to set email alerts
|

Types of work-related behavior and experiences and stress coping strategies among single mothers and mothers in relationships differentiating role of work satisfaction

Abstract: Objectives: The purpose of the study has been to describe functioning of single and mothers in relationships (married or in informal relationships) at work and verify if the declared degree of work satisfaction differentiates types of behavior at work and stress coping strategies in both groups of mothers. Material and Methods: The study was conducted on equal samples of single mothers (N = 186) and mothers from 2-parent families (N = 186) using Latack Coping Scale that measures work-related stress coping stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
(26 reference statements)
2
14
0
Order By: Relevance
“…The research to date indicates that working women who are willing to seek help and support are more satisfied with their work, which is, to them, more subjectively important [7]. The obtained results confirm that observation also in reference to working women whose family situation is varied, as both bigger available and received support, and a bigger level of satisfaction with support is connected with generally higher satisfaction with work in that group.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The research to date indicates that working women who are willing to seek help and support are more satisfied with their work, which is, to them, more subjectively important [7]. The obtained results confirm that observation also in reference to working women whose family situation is varied, as both bigger available and received support, and a bigger level of satisfaction with support is connected with generally higher satisfaction with work in that group.…”
Section: Discussionsupporting
confidence: 73%
“…The research, the aim of which has been to describe functioning at work in the case of single and married mothers, and to determine if the declared level of satisfaction with work differentiates types of behavior and experiences at work as well as stress coping strategies in these groups has shown that interaction of satisfaction with work and type of mothers significantly differentiated only one stress coping strategy: one of resignation. This strategy was more frequently applied by single mothers whose satisfaction with work was lower; there was a significant difference between them and the single and married mothers with a higher level of satisfaction with work, regardless of their satisfaction with work [7]. The quality and the amount of support needed by single mothers to satisfyingly combine work and the role of mother in the light of research and scientific observation is still to be determined.…”
Section: Satisfaction With Workmentioning
confidence: 99%
“…Our findings established statistically significant relationships between resilience, quality of life, and physical and mental health. Following other findings (Cairney et al, 2003;Lansford et al, 2001;Napora et al, 2018), single mothers were more likely to express symptoms of depression, experience reduced satisfaction with life and have lower self-esteem in comparison to married mothers. They were also less likely to seek help when addressing work-related stress.…”
Section: Discussionsupporting
confidence: 62%
“…However, single mothers were more likely to express symptoms of depression, reduced satisfaction with life and lower self-esteem in comparison to married mothers (Cairney, Boyle, Offord, & Racine, 2003;Lansford, Ceballo, Abbey, & Stewart, 2001). They were also less likely to seek help when addressing work-related stress (Napora et al, 2018).…”
mentioning
confidence: 91%
“…Existing research reveals that women satisfied with their job are more likely to cope with setbacks by seeking help, and that work is of greater subjective importance to them (Napora, Andruszkiewicz, & Basińska, 2018). Furthermore, previous research indicates a connection between job satisfaction and other factors influencing their functioning in the family (Mróz & Kaleta, 2015).…”
mentioning
confidence: 99%